2016
DOI: 10.1159/000443997
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Microbial Degradation of Hydrocarbons: From Enzymatic Reactions to the Environment

Abstract: Hydrocarbons are abundant in anoxic environments and pose biochemical challenges to their anaerobic degradation by microorganisms. Within the framework of the Priority Program 1319, investigations funded by the Deutsche Forschungsgemeinschaft on the anaerobic microbial degradation of hydrocarbons ranged from isolation and enrichment of hitherto unknown hydrocarbon-degrading anaerobic microorganisms, discovery of novel reactions, detailed studies of enzyme mechanisms and structures to process-oriented in situ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 645 publications
(162 citation statements)
references
References 49 publications
(35 reference statements)
1
158
0
3
Order By: Relevance
“…Thus, they are suggested to rely on O 2 formed via NO dismutation to activate and oxidize hydrocarbons when growing under nitrate-and nitritereducing conditions. Methane and alkanes are among the most stable compounds that require high energy for activating the first C-H bond (33). Therefore, it can be speculated that O 2 formed via NO dismutation could provide a competitive advantage for oxygenic denitrifiers thriving on recalcitrant compounds in anoxic environments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are suggested to rely on O 2 formed via NO dismutation to activate and oxidize hydrocarbons when growing under nitrate-and nitritereducing conditions. Methane and alkanes are among the most stable compounds that require high energy for activating the first C-H bond (33). Therefore, it can be speculated that O 2 formed via NO dismutation could provide a competitive advantage for oxygenic denitrifiers thriving on recalcitrant compounds in anoxic environments.…”
Section: Discussionmentioning
confidence: 99%
“…2016; Rabus et al. 2016). The enzymes involved in the anaerobic pathways have been described in detail (for a review, see Meckenstock et al.…”
Section: Microbial Pah Degradationmentioning
confidence: 99%
“…For the carboxylation route, a carboxylase belonging to the UbiD-like proteins family is proposed for the carboxylation of the aromatic ring (Rabus et al. 2016). For the methylation route, it is proposed to proceed via a methyl-transferase that methylates the aromatic ring (Safinowski and Meckenstock 2006) and then a naphthyl-2-methyl-succinate synthase, a glycyl-radical-containing enzyme, catalyses the addition to fumarate (Meckenstock and Mouttaki 2011).…”
Section: Microbial Pah Degradationmentioning
confidence: 99%
“…Experimentally it has been shown that 1 (2). A higher energy barrier has been calculated for reaction with adenine, giving for the first time an explanation of the lack of reactivity of 1 O 2 toward adenine.…”
Section: Working Group 2: Models Of Dna Damage and Consequencesmentioning
confidence: 90%
“…biosynthetic pathways to antibiotics and cofactors. In addition to this medical context, radical enzymes are essential for the degradation of alkanes and aromatic hydrocarbons derived not only from natural processes, but also as a result of environmental damage from oil spills and other industrially caused pollution [1]. The primary objectives of WG1 were:…”
Section: Working Group 1: Radical Enzymesmentioning
confidence: 99%